Abstracts (Edited By Dr. Qasim Lateef Chaudhry) - Chaudhry, Qasim Lateef (Pakistan Journal of Ophthalmology, 2018)
Treatment of coats’ disease with intravitreal bevacizumab Ray R, David E Barañano, G Baker Hubbard Br J Ophthalmo. 2013; 97: 272–7. Lesions simulating retinoblastoma (pseudoretinoblastoma) in 604 cases results based on age at presentation Shields CL, Schoenberg E, Kocher K, Shukla SY, Kaliki S, Shields JA Ophthalmology. 2013; 120: 311-6. Long-term rejection incidence and reversibility after penetrating and lamellar keratoplasty Guilbert E, Bullet J, Sandali O, Basli E, Laroche L, Borderie VM Am J Ophthalmol. 2013; 155: 560–569 The effect of an ahmed glaucoma valve implant on corneal endothelial cell density in children with glaucoma secondary to uveitis Ayuso VK, Scheerlinck LM, Boer JD Am J Ophthalmol. 2013; 155: 530–5.